1984
DOI: 10.1007/bf01131622
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic assessment of endometrial changes in stimulated cycles in an in vitro fertilization and embryo transfer program

Abstract: Four distinct patterns in the ultrasonic appearance of preovulatory endometrium can be identified and described in patients undergoing stimulated cycles in an in vitro fertilization program. Ultrasonically, this endometrial response can be seen as a quantitative change in thickness and a qualitative change in gray-scale appearance or reflectivity. The application of this additional parameter of endometrial assessment together with the conventional measurement of follicular diameter as a means of optimally timi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(40 citation statements)
references
References 7 publications
1
37
1
1
Order By: Relevance
“…The endometrial thickness in the peri-ovulatory phase is significantly greater when the IVF cycle results in pregnancy [44][45][46]. A hypoechogenic endometrium surrounded by a hyperechogenic cavity and junction lines is also significantly more frequently observed in the event of success [46,47].…”
Section: Doppler Ultrasonography Of the Endometrium And Implantationmentioning
confidence: 86%
“…The endometrial thickness in the peri-ovulatory phase is significantly greater when the IVF cycle results in pregnancy [44][45][46]. A hypoechogenic endometrium surrounded by a hyperechogenic cavity and junction lines is also significantly more frequently observed in the event of success [46,47].…”
Section: Doppler Ultrasonography Of the Endometrium And Implantationmentioning
confidence: 86%
“…In their experience, the five-line appearance was the most likely to be associated with implantation. Smith et al 25 felt that both endometrial thickness and pattern were important. Other investigators have also looked at the relationship between endometrial thickness or texture and outcomes.…”
Section: Jsafogmentioning
confidence: 99%
“…They are considered to be useful in deciding on receptivity in IVF.The Smith system is as follows 6,25 • Grade I: Hyperechoic The spiral arteries respond to the hormonal changes of the menstrual cycle and undergo transformations, as well. These responses include proliferation of the endothelium, thickening of the wall and coiling.…”
Section: Endometrial Patternmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, intermediate patterns are often discarded and the endometrium is simply described as multilayered or non-multilayered (Sher et al, 1991;Smith et al, 1984). In a prospective study, Serafimi et al(1994) found the multilayered pattern to be more predictive of implantation than any other parameter measured.…”
Section: Endometrial Patternmentioning
confidence: 99%